Enacting Reflection: A New Approach to Workplace Complexities. Issue 3 (August 2020) - Justice, Sean; Morrison, Emily; Yorks, Lyle
The Problem: Change has changed, and workplaces are grappling with new complexities and ambiguities. Human resource development (HRD) scholar-practitioners are called upon to help workplaces learn to navigate these changes; however, traditional approaches have limited utility when dealing with dynamic, emergent change. To address these limitations, scholars have proposed adopting enactive approaches that are rooted in systems thinking and complexity theories, but there is limited understanding of what this means in HRD practice. The Solution: This article explores HRD responses to change from an enactive perspective. Enactivism suggests that people create their context through engagement with physical and social environments. From this perspective, reflection is not necessarily "on" experience, as if somehow separate from it. Rather, reflection is active engagement in, by, and through experience. This article aims to expand theoretical understanding and practical applications of enactivism in workplace learning. The Stakeholders: HRD scholar-practitioners seeking new options for navigating workplace learning complexities.